Responsibility ina Time of AIDS: A Pastoral Responsebility Catholic Theologians and AIDS Activists in Southern Africa. - Bate, Stuart C (Cluster Publications; Catholic Theological Society of Africa; SACBC AIDS Office; St Augustine College of South Africa, 2003)
Responsibility in a time of AIDS: a pastoral response by Catholic theologians and AIDS activists in Southern Africa